1998
DOI: 10.1007/s004020050212
|View full text |Cite
|
Sign up to set email alerts
|

The Furlong hydroxyapatite-coated femoral prosthesis

Abstract: We report the clinical and radiograph outcome of 77 Furlong hydroxyapatite fully coated femoral prosthesis in 71 patients undergoing primary total hip replacement, with mean follow-up of 65 months (range 48-82 months). The patients' average age at surgery was 55 years. The clinical results, as determined by Harris hip score, were excellent or good for 84% of the hips. Thigh pain which was not disturbing was present in 9% of the hips. No femoral component had been revised for aseptic loosening, and none were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The promising results produced by HA-coated femoral components have been repeated in the younger patient. Loupasis et al [15], in a six year follow-up study of 45 patients under the age of 50, reported no revision for aseptic loosening or evidence of stem loosening. Capello et al [3] reported a low stem failure rate of 2% in patients below 45 years of age when using a proximally HA-coated implant with a minimum follow-up of ten years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising results produced by HA-coated femoral components have been repeated in the younger patient. Loupasis et al [15], in a six year follow-up study of 45 patients under the age of 50, reported no revision for aseptic loosening or evidence of stem loosening. Capello et al [3] reported a low stem failure rate of 2% in patients below 45 years of age when using a proximally HA-coated implant with a minimum follow-up of ten years.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of young in patient outcome studies of hip arthroplasty in the literature varies, but in this contex, young generally refers to patients younger than 50 years, and there are few reports of hip prosthesis in patients younger than 30 years of age at the time of implantation [6]. The use of a hydroxyapatite (HA)-coated cementless stem in THR is well established [15], and our clincal experiences with a HA-coated stem are, in general, very good [21]. The aim of this study was, therefore, to evaluate the long-term clinical and radiological outcomes of a HA-coated femoral stem implanted in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…While many surgeons presume proximally coated stems, or cemented stems, have a lower incidence of thigh pain than fully coated stems, this remains controversial [1,2,17,25,28,30,38]. Most authors recognize the reported incidence of thigh pain will be influenced by the way a patient is asked about its presence, a point best controlled with a prospective randomized blinded clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] An HAC-coated implant also has the potential for adaptive stress transfer at the prosthesis-bone interface, and good early clinical results have been reported following the use of HACcoated implants. 5,[10][11][12][13] Primary stability is important with cementless THR because a reduction in micromovement improves osseo-integration between the implant and bone and reduces migration. Such primary stability is provided by the design features, of which there is great variability in contemporary cementless stems.…”
mentioning
confidence: 99%